EMPLOYEE PERFORMANCE IMPACTED BY WORK ENVIRONMENT AND COMPENSATION THROUGH LOYALTY AT PUSKESMAS CERME - Utari, Woro; Muliyani, Suci (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
This study aims to identify the significant influence of the work environment and salary on employee performance at Cerme Public Health Center. The sample consists of 50 employees from various divisions of Cerme Public Health Center, selected using the Proportional Random Sampling technique. This research employs an explanatory method with a quantitative approach, and data were collected through questionnaires. Data analysis was conducted using Partial Least Square (PLS) to test both direct and indirect effects through outer and inner model testing. The results indicate that the work environment has a positive and significant impact on loyalty; compensation also has a positive and significant effect on loyalty, and performance is positively and significantly influenced by the work environment, compensation, and loyalty. Additionally, there is a strong and mutually beneficial relationship between the work environment and salary in influencing employee performance through loyalty.